2019
DOI: 10.1136/ijgc-2018-000013
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of residual disease in advanced stage malignant ovarian germ cell tumors

Abstract: ObjectiveTo investigate the prognostic significance of complete gross resection following cytoreductive surgery for patients with advanced stage malignant ovarian germ cell tumors.MethodsThe National Cancer Data Base was accessed and patients diagnosed with an advanced stage (II-IV) malignant ovarian germ cell tumor who underwent primary cytoreductive surgery between 2011 and 2014 were selected for further analysis. For analysis purposes two groups were formed: patients with complete gross resection and those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Because the peak incidence of NGOC occurs among adolescents and women of reproductive age, fertility-preserving treatment should be considered in patients with early-stage cancer. Although complete cytoreduction (R0) has been reported to be an independent prognostic factor[ 13 ], it is still controversial whether patients with advanced disease can be offered fertility-preserving surgery. Inaba et al [ 14 ] have reported that patients with advanced disease, with the correct diagnosis, rational treatment, and strict surveillance of serum β-hCG, can often receive fertility-sparing treatment and achieve long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Because the peak incidence of NGOC occurs among adolescents and women of reproductive age, fertility-preserving treatment should be considered in patients with early-stage cancer. Although complete cytoreduction (R0) has been reported to be an independent prognostic factor[ 13 ], it is still controversial whether patients with advanced disease can be offered fertility-preserving surgery. Inaba et al [ 14 ] have reported that patients with advanced disease, with the correct diagnosis, rational treatment, and strict surveillance of serum β-hCG, can often receive fertility-sparing treatment and achieve long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, fertility-sparing surgery was attempted whenever possible after initial diagnosis and 83.6% of patients achieved complete surgical resection. Some studies have shown that maximal debulking surgery is significantly associated with improved overall survival [21,22], while others have not [23,24]. Considering the chemotherapy-sensitive nature of MOGCTs, fertility-sparing cytoreductive surgery seems reasonable for patients in advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the level of AFP at diagnosis was not significantly associated with survival or recurrence. A recent study focused on patients diagnosed with advanced stage (II–IV) MOGCT submitted to primary cytoreductive surgery [32]. The authors reported no difference in OS following stratification by histology for dysgerminoma or non-dysgerminoma.…”
Section: Prognostic Factorsmentioning
confidence: 99%